ANALISIS VOLUME EKSPOR KARET ALAM INDONESIA KE PASAR INTERNASIONAL PERIODE 1990-2022 - Nainggolan, Kristina; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 14 No 1 (2025): Vol.14.No.1. JANUARI 2025 [1-122]DO - 10.24843/EEP.2025.v14.i01.p04, 2025)
Rubber makes a major contribution as a source of trade in empowering financial development in Indonesia. This research was conducted to analyze the factors that influence the volume of Indonesian natural rubber exports to the international market, namely international natural rubber prices, the US Dollar exchange rate, Indonesian natural rubber production, and the area of Indonesian natural rubber land as well as the structure of the Indonesian rubber market. Data analysis uses multiple linear regression analysis methods with the E-Views tool. The source of information in this examination is additional information involving time series information for 33 years for each variable from 1990 to 2022. The results of this research state that the structure of the Indonesian rubber market is oligopsonistic. The international price of Indonesian natural rubber, the US dollar exchange rate, the amount of Indonesian natural rubber production, and the area of Indonesian natural rubber land simultaneously influence the volume of Indonesian natural rubber exports to the international market. The amount of production has a positive and significant effect, while the international price of natural rubber in the US Dollar exchange rate and land area has a negative but not significant effect on the volume of natural rubber exports. keyword: Exports, Rubber, price, exchange rate, production, land area